2018
DOI: 10.1007/s13577-018-0215-0
|View full text |Cite
|
Sign up to set email alerts
|

MiR-323a-3p suppressed the glycolysis of osteosarcoma via targeting LDHA

Abstract: Accumulating evidence has demonstrated that there is critical involvement of miRNAs in the initiation and progression of cancers. Here, we showed that miR-323a-3p was significantly down-regulated in osteosarcoma (OS) tissues and cell lines. Overexpression of miR-323a-3p decreased the cell viability, colon formation and induced the apoptosis of OS cells. Using bioinformatics analysis, lactate dehydrogenase A (LDHA) was predicted as one of the down-steam targets of miR-323a-3p. Highly expressed miR-323a-3p signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…MicroRNA (miRNA), a kind of small non‐coding RNA, could inhibit translation or promote degradation of targets via combining to the specific region of 3′‐untranslated region (3′‐UTR) in targeted mRNA . Until now, several miRNAs like miR‐34a, miR‐34c, miR‐369‐3p, miR‐374a, miR‐30a‐5p, miR‐142‐3p, miR‐30d‐5p, miR‐323a‐3p, miR‑199a‑3p, miR‐449a, and miR‐4524a/b have been found to target the mRNA of LDHA . In a recent study on colorectal cancer, miR‐34a, miR‐34c, miR‐369‐3p, miR‐374a, and miR‐4524a/b were established to directly inhibit LDHA .…”
Section: Regulation Modes Of Ldhamentioning
confidence: 99%
“…MicroRNA (miRNA), a kind of small non‐coding RNA, could inhibit translation or promote degradation of targets via combining to the specific region of 3′‐untranslated region (3′‐UTR) in targeted mRNA . Until now, several miRNAs like miR‐34a, miR‐34c, miR‐369‐3p, miR‐374a, miR‐30a‐5p, miR‐142‐3p, miR‐30d‐5p, miR‐323a‐3p, miR‑199a‑3p, miR‐449a, and miR‐4524a/b have been found to target the mRNA of LDHA . In a recent study on colorectal cancer, miR‐34a, miR‐34c, miR‐369‐3p, miR‐374a, and miR‐4524a/b were established to directly inhibit LDHA .…”
Section: Regulation Modes Of Ldhamentioning
confidence: 99%
“…MiR-383 functioned as an inhibitor on the proliferation of ovarian cancer cell by targeting LDHA and suppressing the glycolysis [27]. A previous study showed that miR-323a-3p inhibited the growth of Osteosarcoma (OS) cell by targeting LDHA and suppressed the glycolysis of OS [28]. These results indicate that LDHA is a potential target of miRNAs to modulate the glucose metabolism of cancers.…”
Section: Discussionmentioning
confidence: 82%
“…Bioinformatics analysis results suggested that LDHA was a target of miR-638, and following luciferase reporter assay and RIP further confirmed the interaction. LDHA is a growth factor and has been proved to regulate cell proliferation and migration of VSMCs [22] Several publications have demonstrated that LDHA are regulated by the miRNAs [26][27][28]. Among these, LDHA promoted glycolysis and cell proliferation of breast cancer MCF-7 and MDA-MB-231 cells, and its beneficial effects on glycolysis and cell proliferation can be impaired by miR-34a [26].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, also miR-323a-3p targets LDH-A and exerts a suppressive role of glycolysis and OS growth. In agreement, miR-323a-3p results significantly downregulated in OS tissues and cell lines, while its overexpression reduces cell viability [150]. In addition, a different miRNA, namely miR-186, which decreases indirectly lactate levels through direct inhibition of HIF-1α and glycolysis, functions as a tumor suppressor of both HOS and U2 OS cell lines, inhibiting tumor cell proliferation and invasion [151].…”
Section: Lactate and Sarcomasmentioning
confidence: 74%